Soldagem com arco submerso utilizando um fluxo com polímero: um estudo da viabilidade de aplicação - Alexandre Manoel da Silva (2017)
Several researches in welding have been carried out the past few years, not only to study the aspects related to existing processes, but also to contribute to the technological development of the process. Studies related to new consumables, equipment and welding techniques were developed, for improvements in products and services. In recent research, a polymer was used as binder of the covered electrodes for use in underwater welding and thereafter in welding out of water in order to achieve impermeability of the coating. The application of the polymer coatings resulted not only in the desired impermeability, but also showed good mechanical properties in the weld metal, with formation of acicular ferrite in amounts greater than the values found in welds performed with conventional coated electrodes. In this work, the polymer was applied as a flux binder for submerged arc welding. As a preliminary experiment, the coating of the impermeable coated electrode was used to produce the granular flux. In the final experiments, three fluxes were produced using the polymer as a virgin flux powder binder and for comparison was used a conventional flux, agglomerated with potassium silicate. The results indicated that the polymer contributed to the reduction of coarse grains in the microstructure and increased at formation of acicular ferrite in the molten zone of the weld metal. Moreover, it was verified that the weld metals deposited with the fluxes produced with polymer presented values of hardness higher than the values found in the weld metals deposited with the conventional flux.